Circularity in Materials: A Review on Polymer Composites Made from Agriculture and Textile Waste - Ali Raza Shafqat; Muzzamal Hussain; Yasir Nawab; Munir Ashraf; Sheraz Ahmad; Ghazia Batool (International Journal of Polymer Science)
Agriculture and textiles have the highest production yields among all sectors to meet mankind’s basic needs, i.e., feeding and clothing; however, they are top contributors to environmental pollution and global waste generation. Their wastes and byproducts are precious organic materials, they have great potential as raw materials for the manufacturing of valuable products. This review sheds light on various textile and agricultural wastes, waste management issues, and their existing utilization. Current waste processing methods are mostly based on waste-to-energy routes or material reclamation; however, both methods are hazardous for the environment and are inefficient. During the past decade, many researchers have utilized agriculture and textile wastes in the fabrication of composites. Textile and agricultural wastes and byproducts can be efficiently used for composite fabrication and can be suitable alternatives to existing raw materials. Using textiles and agricultural wastes for composite manufacturing can not only address waste management issues and replace non-eco-friendly materials in the composite industry but also significantly improve composite properties.